AN ANALYSIS ON EMPLOYEE PERFORMANCE IN THE TECHNICAL SERVICE DIVISION AT PT X - Annisa Mumtaz; Sulastri Irbayuni; Sugito (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the effect of workload and communication on employee performance in the technical service division. Employee performance refers to the results achieved by individuals in carrying out their duties in accordance with the operational standards set by the company. The method used in this study employs a quantitative approach. The study population consists of 48 employees, using a saturated sampling technique where all employees are included as samples. The data collected is primary data, obtained through questionnaires and interviews, and the data is processed and analyzed using Partial Least Square (PLS). The results of the study indicate that workload contributes to employee performance, as does communication. This study is expected to provide benefits for companies to pay more attention to workload and communication to improve employee performance.